KONSEP KURIKULUM BERBASIS CINTA DALAM PERSPEKTIF HADIS: IMPLEMENTASI KURIKULUM BERBASIS CINTA DI MADRASAH - Muhammad Mukhtar. S; La Ode Ismail Ahmad; Abdul Rahman Sakka (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
This study originates from Indonesia’s urgent need for an educational model capable of reducing radicalism and polarization while fostering an inclusive, humanistic, and moderate understanding of religion. The Love-Based Curriculum is viewed as an approach that positions religious teaching as a means to cultivate humanity, tolerance, and compassion, rather than as a justification for exclusivist attitudes. This research aims to examine the concept of the Love-Based Curriculum from the perspective of Hadith and its implementation in madrasahs. The method employed is a literature study using descriptive-analytical and thematic, approaches, drawing on both primary and secondary sources. The findings indicate that, from the Hadith perspective, the Love-Based Curriculum emphasizes the importance of transforming educational paradigms based on the value of compassion as well as balancing vertical relationships, love for Allah and His Messenger and horizontal relationships, love for fellow humans, knowledge, and the homeland. This curriculum aims to develop individuals who are humanistic, nationalistic, naturalistic, and tolerant, making love a fundamental principle of life. Its implementation in madrasahs is carried out by integrating the values of love into intracurricular, cocurricular, and extracurricular activities, grounding all educational practices in love for Allah, the Messenger, knowledge, humanity, the environment, and the homeland